Sex differences in endothelial glycocalyx thickness and the response to glycocalyx‐targeted therapy among older adults - Colin J. Gimblet; Anthony J. Donato; Diana I. Jalal; Gary L. Pierce (Physiological Reports, 2025)
Abstract Endothelial glycocalyx thickness declines with age, potentially increasing cardiovascular disease risk. However, sex differences in glycocalyx thickness and responses to glycocalyx‐targeted therapies remain unclear. This post hoc analysis examined sex differences in glycocalyx thickness and the effects of Endocalyx Pro supplementation in older adults. We analyzed data from 22 participants in a prior clinical trial (NCT06071728) that assessed 12‐week Endocalyx Pro (3712 mg/day) supplementation on vascular function. Glycocalyx thickness was estimated as the perfused boundary region (PBR) using the GlycoCheck, with higher PBR indicating smaller glycocalyx thickness. Postmenopausal females had higher PBR 4–25 than older males (2.11 ± 0.14 vs. 1.97 ± 0.13 μm; p = 0.02), particularly in microvessels 9–17 μm in diameter. Male sex (B [95% CI], −0.14 [−0.26, −0.02]; p = 0.02) and body mass index (BMI) (B [95% CI], −0.02 [−0.04, −0.01]; p = 0.01) were associated with lower PBR 4–25 in univariate analyses; however, when included in a multivariate model, the association with sex was attenuated (p = 0.15), while BMI remained significant (p = 0.04). After 12 weeks of Endocalyx Pro, PBR 4–25 increased in older males (+0.087 ± 0.148 μm) but decreased in postmenopausal females (−0.178 ± 0.148 μm; p = 0.009). In conclusion, we observed that postmenopausal females had smaller glycocalyx thickness, partially explained by BMI, and demonstrated a greater improvement with Endocalyx Pro, suggesting sex‐specific therapy effects.